PENERAPAN METODE PEMBELAJARAN BRAINSTORMING DALAM MENINGKATKAN HASIL BELAJAR MATA PELAJARAN BAHASA INDONESIA PADA SISWA KELAS V SDN 164319 TEBING TINGGI - Rismawaty Tampubolon (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
The aim of this research is to improve learning result on Indonesian Language subject  through brainstorming method. This classroom action research conducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from grade V, SD Negeri 164319 Tebing Tinggi which amounted to 33 students. This study used a qualitative descriptive analysis technique. The results showed that the method of  the brainstorming in Indonesian Language subject can improve student learning result characterized by increased mastery learning students, namely pre-cycle (69,7%), the first cycle (81,8%), cycle II (90,9 %) and complete learn the clasical equal to 90,9 %.Keywords: Brainstorming, Indonesian Language